Environmental education on the European Green Deal. Implications and promotion of the concept through different channels in Romania - Ionel Bran (Journal of Research and Innovation for Sustainable Society)
There is a visible urgent need to move from a linear economy to a circular economy in order to meet the requirements of the European Green Deal agenda. Recently, Romania implemented the DSR, getting in line with other countries that have had this system for many years. Therefore, the implementation of the Green Deal should also be focused on the promotion of the concept, how the information arrives at the citizens, how people are educated in schools and high schools regarding sustainability, etc. Focusing on the topic, this article aims to investigate the level of environmental education held by Romanians regarding the European Green Deal. This study was exploratory market survey research based on a questionnaire, focusing only on Romanian citizens who are living in Romania. Therefore, a quantitative research design was used on a sample of 111 Romanians and the results show that the respondents are satisfied with the DSR in Romania. In addition, it was found a strong positive correlation between the respondents’ environmental education gained through different channels or methods from the private and public sectors and their behavior regarding sustainability. In the end, it was found that there was a statistically significant difference between the people who already knew what the Green Deal meant and the people who didn’t when it came to their sustainability behavior. So, in conclusion, people who already knew what the Green Deal meant showed a more sustainable behavior. The results suggest the importance of boosting the promotion of the European Green Deal, sustainability, circular economy, and so on, reaching more people, thus creating a more powerful educational system in this direction. The paper could serve as well as a starting point for future academic research and for private entities and Romanian public institutions and authorities to strengthen collaboration and create more common projects on sustainability.